How Phytophthora cinnamomi became associated with the death of Eucalyptus marginata – the early investigations into jarrah dieback - Davison, Elaine (Springer, 2015)
The name jarrah dieback was used in the 1940s to describe a serious economic problem in the jarrah forest in the south west of Western Australia. This was the sudden death of groups of jarrah (Eucalyptus marginata) trees that occurred on previously logged sites that had a tendency to become waterlogged in winter. Although the cause was not determined at the time, from symptoms recorded in early investigations the most likely explanation is that the trees died as the result of waterlogging damage. In the 1960s it was shown that many of these sites were infested by the introduced oomycete Phytophthora cinnamomi and tree deaths, together with the deaths of many mid- and under-storey plants, were attributed to this pathogen. A chronology of the research, based on contemporary unpublished documents, shows that in 1968 the conclusion that P. cinnamomi caused jarrah deaths was not supported by the available evidence, because the work did not satisfy the first and fourth of Koch’s postulates. The evidence that P. cinnamomi killed many mid- and under-storey plants was much stronger. There are two problems that have been confused: the death of groups of jarrah trees (jarrah dieback) that is caused by waterlogging and the death of many mid- and under-storey plants (Phytophthora dieback) caused by P. cinnamomi infection.